Psychodynamics in Information Communication Technology and Perception of Science Teachers and Students: Evidence from Karachi - Muhammad Yousuf Sharjeel (International Islamic University Islamabad, 2019)
Pedagogic life in the twenty-first century has embraced many impeding changes and advancement and college teaching has equally endeavored to embrace such advancements. Information and communication technology (ICT) has had a great impact on teaching and learning methodology of Grade XI Physics. Learning the subject contents of Grade XI Physics has been an arduous task for most college students in Karachi. It is also noted that ICT-based Physics education enhances the professional development and performance of the teachers who teach the contents of Sindh Textbook Board. Articles, problem-solving questions, derivations and other concepts in physics seem difficult to comprehend to many science group Grade XI students. The introduction and use of ICT in teaching and learning Physics for teachers and students seems to have made teaching interesting for many teachers. This paper looks into such assumptions and examines the extent to which ICT can make significant contributions in promoting effective teaching of Grade XI Physics. A random sample of n= 149 colleges was drawn from the colleges listed with the Sindh region located in the city of Karachi. The study finds significant impact of ICT on teacher’s professional performance and draws the conclusion that ICT-based teaching of Grade XI Physics can enhance the performance of students and teachers.